New Zealand's Diaspora and Overseas-born Population - John Bryant; David Law (New Zealand Government, The Treasury, 2004)
Many New Zealand-born people migrate overseas, creating a diaspora, and many overseas-born people migrate to New Zealand. Both the diaspora and the overseas-born population in New Zealand may facilitate the international exchange of goods and ideas. Much discussion of international linkages has, however, been limited by a lack of data on numbers of people involved. Based mainly on place-of-birth data from national censuses, this paper provides estimates of the size and structure of New Zealand's diaspora and overseas-born population, as well as comparisons with selected OECD countries such as Australia. A tentative conclusion is that the potential contribution of New Zealand's diaspora may have been overestimated, and the contribution of the overseas-born population underestimated.
Keywords: F22; J19; 330; International migration; diaspora; measurement; New Zealand; Australia; population; emigration; immigration